Interaction of vitamin D with membrane-based signaling pathways - Larriba, María Jesús; González-Sancho, José Manuel; Bonilla, Félix; Muñoz, Alberto (Frontiers in Physiology, 2014)
Many studies in different biological systems have revealed that 1alpha,25-dihydroxyvitamin D3 (1alpha,25(OH)2D3) modulates signaling pathways triggered at the plasma membrane by agents such as Wnt, transforming growth factor (TGF)-beta, epidermal growth factor (EGF) and others. In addition, 1alpha,25(OH)2D3 may affect gene expression by paracrine mechanisms that involve the regulation of cytokine or growth factor secretion by neighboring cells. Moreover, post-transcriptional and post-translational effects of 1alpha,25(OH)2D3 add to or overlap with its classical modulation of gene transcription rate. Together, these findings show that vitamin D receptor (VDR) cannot be considered only as a nuclear-acting, ligand-modulated transcription factor that binds to and controls the transcription of target genes. Instead, available data support the view that much of the complex biological activity of 1alpha,25(OH)2D3 resides in its capacity to interact with membrane-based signaling pathways and to modulate the expression and secretion of paracrine factors. Therefore, we propose that future research in the vitamin D field should focus on the interplay between 1alpha,25(OH)2D3 and agents that act at the plasma membrane, and on the analysis of intercellular communication. Global analyses such as RNA-Seq, transcriptomic arrays and genome-wide ChIP are expected to dissect the interactions at the gene and molecular levels.